Method for synthesizing titanium oxide nanoparticles through mild hydrothermal method and application
A mild hydrothermal method using hydrogen peroxide and ammonia solution addresses the synthesis challenges of titanium oxide nanoparticles, resulting in improved particle uniformity and electrical properties that enhance the performance of perovskite solar cells.
Patent Information
- Application Number
- CN202411026316.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-30
- Publication Date
- 2024-12-20
AI Technical Summary
Existing methods for synthesizing titanium oxide nanoparticles are cumbersome, energy-intensive, and result in uneven particle sizes and poor electrical properties, leading to low battery voltage and filling factor in perovskite solar cells.
A mild hydrothermal method using hydrogen peroxide and ammonia solution to form a uniform complex precursor, adjusting pH to convert rutile phase to anatase phase, and synthesizing nanoparticles at 200°C for improved crystallinity and electron mobility.
The method produces uniformly sized titanium oxide nanoparticles with high crystallinity and fewer defects, enhancing current density and voltage in perovskite solar cells by promoting anatase phase formation.
Smart Images

Figure CN119160934A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of nano materials, and in particular to a method for synthesizing titanium oxide nanoparticles using a mild hydrothermal method and application thereof. Background Art
[0002] In order to achieve sustainable utilization and development of energy, various new energy sources such as hydropower, wind power, bioenergy, solar energy, etc. have been developed. Among them, stable printable mesoscopic perovskite solar cells have emerged in recent years and have achieved gratifying results. Printable mesoscopic perovskite solar cells use three layers of printed films of C, ZrO2, and TiO2 / SnO2 as the battery skeleton, and then fill the perovskite solution into the mesopores of the printed film and anneal and crystallize. The basic principle is that perovskite absorbs light to generate electromotive force by photovoltaic effect. Cheap and conductive C is used as the back electrode, ZrO2 with good insulation is used as the spacer layer, and TiO2 / SnO2 is used as the electron transport layer. Among these three important components, the role of the electron transport layer is particularly important, and it plays the role of electron transfer. An excellent electron transport layer should have high electron mobility, carrier concentration, small effective electron mass, and energy band matching with perovskite. Titanium dioxide, as a common semiconductor, has a suitable band gap that can absorb ultraviolet light and part of visible light, and has a conduction band position that matches the perovskite energy band. However, it has always been a difficult problem to synthesize titanium oxide nanoparticles with suitable and uniform particle size and good electrical properties.
[0003] The reported preparation methods of titanium oxide nanoparticles usually have the following disadvantages: the preparation method is cumbersome, the high hydrothermal temperature leads to high energy consumption and increased risk factor. The particle size of the synthesized particles is uneven, and the battery voltage (0.867) and filling factor (0.67) are both low. The preparation methods of titanium oxide nanoparticles need to be further improved. Summary of the invention
[0004] The present invention aims to solve at least one of the technical problems in the related art to a certain extent. The present invention provides a method for synthesizing titanium oxide nanoparticles by a mild hydrothermal method. The method provided forms a uniform complex precursor solution through the peroxide bond in hydrogen peroxide and Ti(OH)4, which ensures the uniformity of the particle size of the titanium oxide particles during the hydrothermal reaction, and the hydrothermal temperature only needs to be around 200 degrees Celsius, which has a sufficiently high safety factor. The titanium oxide nanoparticles synthesized in this way have high crystallinity and fewer surface defects, so there are fewer electron-hole pairs and a higher voltage (about 1.0000v±0.0200).
[0005] Specifically, the present invention provides the following technical solutions:
[0006] The first aspect of the present invention provides a method for synthesizing titanium oxide nanoparticles by a mild hydrothermal method, comprising:
[0007] (1) Under low temperature conditions, TiCl4 is added dropwise to deionized water, and after stirring, an ammonia solution is added dropwise to obtain Ti(OH)4 solid;
[0008] (2) washing the Ti(OH)4 solid by dripping with a Buchner funnel and dispersing it with deionized water to obtain a precursor dispersion;
[0009] (3) Under low temperature conditions, hydrogen peroxide is added dropwise to the precursor dispersion, and then an ammonia solution is added to adjust the pH value to 5.5-6.5, and hydrothermally heated at a predetermined temperature to obtain titanium oxide nanoparticles, wherein the predetermined temperature is 190-210 degrees Celsius.
[0010] The method provided by the present invention can hydrothermally synthesize uniformly dispersed titanium oxide nanoparticles with uniform and suitable particle sizes at about 200 degrees Celsius, and is applied to mesoporous printed perovskite solar cells to improve the current density and voltage of the battery. In addition, the present invention adjusts the crystal phase of the titanium oxide nanoparticles by adding an ammonia solution to increase the pH value of the precursor solution before hydrothermal treatment, so that the rutile phase titanium oxide is completely converted into anatase phase titanium oxide with good crystallization, thereby improving the current of the perovskite solar cell.
[0011] According to an embodiment of the present invention, the method for synthesizing titanium oxide nanoparticles by mild hydrothermal method described above may further include the following technical features:
[0012] According to an embodiment of the present invention, the ammonia solution in step (1) is an ammonia solution having a volume concentration of 40 v / v% to 60% v / v;
[0013] According to an embodiment of the present invention, the ammonia solution in step (3) is an ammonia solution with an ammonia volume concentration of 40 v / v% to 60% v / v.
[0014] According to an embodiment of the present invention, the low temperature condition in step (1) is 0 to 4 degrees Celsius.
[0015] According to an embodiment of the present invention, the low temperature condition in step (3) is 0 to 4 degrees Celsius.
[0016] According to an embodiment of the present invention, the mass fraction of the hydrogen peroxide in step (3) is 25 w / w% to 35 w / w%.
[0017] According to an embodiment of the present invention, the particle size of the titanium oxide nanoparticles is 20 to 70 nanometers, preferably 25 to 60 nanometers.
[0018] According to an embodiment of the present invention, the predetermined temperature is 195-205 degrees Celsius, preferably 200 degrees Celsius.
[0019] The second aspect of the present invention provides a titanium oxide nanoparticle prepared according to the method described in any embodiment of the first aspect.
[0020] The third aspect of the present invention provides a conductive paste comprising the titanium oxide nanoparticles described above.
[0021] A fourth aspect of the present invention provides a titanium oxide nanofilm, which is prepared using the conductive paste described above.
[0022] A fifth aspect of the present invention provides a perovskite solar cell, comprising:
[0023] Basal layer;
[0024] A hole blocking layer, the hole blocking layer is located on the surface of the base layer, and the hole blocking layer contains the titanium oxide nano film surface mentioned above;
[0025] A mesoporous electron transport layer, wherein the mesoporous electron transport layer is located on the surface of the hole blocking layer;
[0026] A mesoporous spacer layer, wherein the mesoporous spacer layer is located on the surface of the mesoporous electron transport layer;
[0027] A porous back electrode layer, wherein the porous back electrode layer is located on the surface of the mesoporous spacer layer; and
[0028] The perovskite film layer is located in the mesopores of the mesoporous electron transport layer, the mesoporous spacer layer and the porous back electrode layer.
[0029] The beneficial effects achieved by the present invention are at least:
[0030] (1) The present invention adopts an economical and mild hydrothermal method to synthesize uniformly dispersed titanium oxide nanoparticles with uniform and suitable particle size, and applies them to mesoporous printed perovskite solar cells, thereby improving the current density and voltage of the battery.
[0031] (2) The present invention increases the pH value of the hydrothermal precursor solution by using an ammonia solution to regulate the crystal phase of titanium oxide nanoparticles, so that the rutile phase titanium oxide is completely transformed into a well-crystallized anatase phase titanium oxide, thereby increasing the current of the perovskite solar cell. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 is a cross-sectional view of a mesoscopic printable perovskite solar cell provided according to an embodiment of the present invention.
[0033] Figure 2 3 is a scanning electron microscope image of the titanium oxide nanofilm provided according to Example 1 of the present invention.
[0034] Figure 33 is an XRD comparison diagram of the titanium oxide nanofilm provided according to Example 1 of the present invention.
[0035] Figure 4 3 is a scanning electron microscope image of the titanium oxide nanofilm provided according to Example 2 of the present invention.
[0036] Figure 5 3 is an XRD comparison diagram of the titanium oxide nanofilm provided according to Example 2 of the present invention. DETAILED DESCRIPTION
[0037] Embodiments of the present invention are described in detail below. Examples of the embodiments are shown in the accompanying drawings. The embodiments described below with reference to the accompanying drawings are exemplary and are intended to be used to explain the present invention, but should not be construed as limiting the present invention.
[0038] As an important component of perovskite solar cells, titanium oxide thin films require titanium oxide particles to have good dispersibility and electrical properties. Therefore, how to obtain titanium oxide thin films with excellent performance has always been a problem that needs to be solved.
[0039] The present invention provides a method for synthesizing titanium oxide nanoparticles by a mild hydrothermal method, comprising:
[0040] (1) Under low temperature conditions, TiCl4 is added dropwise to deionized water, and after stirring, an ammonia solution is added dropwise to obtain Ti(OH)4 solid;
[0041] (2) washing the Ti(OH)4 solid by dripping with a Buchner funnel and dispersing it with deionized water to obtain a precursor dispersion;
[0042] (3) Under low temperature conditions, hydrogen peroxide is added dropwise to the precursor dispersion, and then an ammonia solution is added to adjust the pH value to 5.5-6.5, and hydrothermally heated at a predetermined temperature to obtain titanium oxide nanoparticles, wherein the predetermined temperature is 190-210 degrees Celsius.
[0043] The method provided by the present invention uses a Buchner funnel to wash Ti(OH)4 to remove excess chloride ions. - As impurity ions, they are doped into the titanium oxide lattice during the hydrothermal process, causing changes in the electrical properties of the nanoparticles. - It will guide the growth of nanoparticles, so removing Cl - It is very necessary. However, if ultrasonic centrifugal washing is used, energy will be transferred to Ti(OH)4, which may cause it to dehydrate and directly form titanium oxide nanoparticles, affecting the nucleation of the final hydrothermal reaction and the uniformity of the product. Therefore, the method of dripping deionized water is finally used to wash Ti(OH)4.
[0044] The method provided by the present invention uses hydrogen peroxide to form a complex with Ti(OH)4 to form a transparent and uniform titanium peroxide complex solution. Such a complex solution can ensure the uniformity of crystal nucleation in a hydrothermal reaction and thus ensure the uniformity of nanoparticles.
[0045] In addition, an ammonia solution is used to adjust the pH value of the titanium peroxide complex solution to adjust the crystal phase of the titanium oxide nanoparticles, causing it to transform from the original anatase phase mainly with a small amount of rutile phase to a pure anatase phase. The effective electron mass of anatase phase titanium oxide is much lower than that of rutile phase, which significantly improves the current of the solar cell after adding ammonia solution to adjust the pH.
[0046] According to a specific embodiment, the ammonia solution in step (1) is an ammonia solution with a volume concentration of 40 v / v% to 60% v / v, for example, an ammonia solution with a volume concentration of 50 v / v%.
[0047] In step (1), when TiCl4 is added dropwise to deionized water, the dropping speed should not be too fast, and can be 1 drop / second. When the ammonia solution is further added dropwise, the dropping speed should be controlled to be slower, for example, 1 drop / 6s.
[0048] According to a specific embodiment, the ammonia solution in step (3) is an ammonia solution with a volume concentration of 40 v / v% to 60% v / v, for example, an ammonia solution with a volume concentration of 50 v / v%. According to a specific embodiment, the volume of the ammonia solution added in step (3) is 1% to 3% of the volume of the precursor dispersion. When too much ammonia solution is added, the photoelectric conversion efficiency of the prepared solar cell device will be reduced, so it should not be too high.
[0049] According to a specific embodiment, the low temperature condition in step (1) is 0 to 4 degrees Celsius. According to a preferred embodiment, it is 0 to 3 degrees Celsius, for example, 0 degrees Celsius, 1 degree Celsius, 2 degrees Celsius, 3 degrees Celsius, etc.
[0050] According to a specific embodiment, the low temperature condition in step (3) is 0 to 4 degrees Celsius. According to a preferred embodiment, it is 0 to 3 degrees Celsius, for example, 0 degrees Celsius, 1 degree Celsius, 2 degrees Celsius, 3 degrees Celsius, etc.
[0051] According to a specific embodiment, the mass fraction of the hydrogen peroxide in step (3) is 25 w / w% to 35 w / w%, for example, 30 w / w%. When the hydrogen peroxide is added dropwise, the dropping speed should not be too fast, for example, 1 drop / 2 seconds.
[0052] According to an embodiment of the present invention, the particle size of the titanium oxide nanoparticles is 20 to 70 nanometers, preferably 25 to 60 nanometers, for example 25 to 50 nanometers.
[0053] The hydrothermal temperature has an effect on the size and morphology of titanium oxide nanoparticles. The predetermined temperature mentioned in the hydrothermal process is about 200 degrees Celsius, which should not be too high or too low. According to an embodiment of the present invention, the predetermined temperature is 195 to 205 degrees Celsius, for example, 195 degrees Celsius, 196 degrees Celsius, 197 degrees Celsius, 198 degrees Celsius, 199 degrees Celsius, 200 degrees Celsius, 201 degrees Celsius, 202 degrees Celsius, 203 degrees Celsius, 204 degrees Celsius, 205 degrees Celsius, etc., preferably 200 degrees Celsius.
[0054] The present invention also provides a titanium oxide nanoparticle, which is prepared according to the above method.
[0055] The present invention also provides a conductive paste comprising the titanium oxide nanoparticles mentioned above.
[0056] The present invention also provides a titanium oxide nano film, which is prepared by using the conductive paste mentioned above.
[0057] In addition, the present invention also provides a perovskite solar cell, which can be referred to Figure 1 As shown, including:
[0058] basal layer;
[0059] A hole blocking layer, the hole blocking layer is located on the surface of the base layer, and the hole blocking layer contains the titanium oxide nanofilm described above;
[0060] A mesoporous electron transport layer, wherein the mesoporous electron transport layer is located on the surface of the hole blocking layer;
[0061] A mesoporous spacer layer, wherein the mesoporous spacer layer is located on the surface of the mesoporous electron transport layer;
[0062] A porous back electrode layer, wherein the porous back electrode layer is located on the surface of the mesoporous spacer layer; and
[0063] The perovskite film layer is located in the mesopores of the mesoporous electron transport layer, the mesoporous spacer layer and the porous back electrode layer.
[0064] The substrate layer mentioned above can be glass or mesoporous zirconium dioxide (ZrO2), etc. Each hole blocking layer, mesoporous electron transport layer, mesoporous spacer layer and perovskite film layer can be prepared by commonly used methods or reagents in the art (the materials used in each layer can be referred to Figure 1 When the substrate layer is a glass surface (non-conductive), it can be used to test the resistivity of the porous back electrode. When the substrate layer is mesoporous zirconium dioxide, the porous back electrode can be used to make a perovskite solar cell. Each layer of the provided perovskite solar cell can be prepared using methods and materials commonly used in the art.
[0065] The technical scheme of the present invention is described below by specific examples. It should be noted that these examples are only used to facilitate the understanding of those skilled in the art and should not be regarded as limiting the scope of protection of the present invention. The reagents used in the experiment, unless otherwise specified, can be obtained by commercial purchase or prepared by the common knowledge of those skilled in the art.
[0066] Chemical raw materials used in the experiment: TiCl4 (AR, 99.0%), ammonia water (analytical grade, AR), 30% hydrogen peroxide (superior grade, GR), ethyl cellulose (9-11 mPa, 45-55 mPa), turpentine alcohol (chemically pure, CP), and anhydrous ethanol (analytical grade, AR).
[0067] Comparative Example 1
[0068] Comparative Example 1 provides a specific method for synthesizing standard titanium oxide nanoparticles. The method specifically comprises the following steps:
[0069] (1) Take a 100 ml jacketed beaker, use a low temperature cooling circulation pump (model DLSB-5L / 20) to pass condensed water, take 15 ml of deionized water and add it. After the water temperature drops to the target temperature, prepare for the next step.
[0070] (2) Under stirring at 500 rpm, add 5 ml of 2M TiCl4 to the deionized water in the first step at a rate of 1 drop / second. After stirring for 10 minutes, use a constant pressure funnel to add 7.2 ml (3.6 ml of ammonia water + 3.6 ml of deionized water) of ammonia solution to obtain a white Ti(OH)4 solid. (When adding the ammonia solution, the drop rate is: 1 drop / 6 seconds; the drop time is: 10 minutes).
[0071] (3) The obtained precursor was quickly transferred to a Buchner funnel lined with two filter papers and a 5000 mesh filter cloth, and washed with deionized water (water drop rate 2 drops / second, washed until the ionic conductivity is 20±5us / cm).
[0072] (4) Use a pump to remove the excess deionized water in the Buchner funnel and transfer it to a 500ml jacketed beaker, add 100ml of deionized water and stir at 500rpm for 20mins to disperse the precursor. Under low temperature conditions, add 50ml of 30% hydrogen peroxide to the precursor dispersion at a rate of 1 drop / 2 seconds at a stirring speed of 350rpm. After 20mins of adding hydrogen peroxide, continue stirring for 20mins. Finally, filter it with a sand core funnel equipped with a 0.2um water filter membrane and transfer it to a polytetrafluoroethylene liner and hydrothermally heat it at 200℃ for 12h to obtain a standard titanium oxide, which is named TiO2-C.
[0073] Example 1
[0074] Example 1 provides a method for synthesizing titanium oxide nanoparticles using a mild hydrothermal method, comprising:
[0075] (1) Take a 100 ml jacketed beaker, use a low temperature cooling circulation pump (DLSB-5L / 20) to pass condensed water, take 15 ml of deionized water and add it. After the water temperature drops to the target temperature, prepare for the next step.
[0076] (2) Under stirring at 500 rpm, add 5 ml of 2M TiCl4 to the deionized water in the first step at a rate of 1 drop / second. After stirring for 10 minutes, use a constant pressure funnel to add 7.2 ml (3.6 ml of ammonia water + 3.6 ml of deionized water) of ammonia solution to obtain a white Ti(OH)4 solid. (During the titration of ammonia solution, the drop rate is 1 drop / 6 seconds; the drop time is 10 minutes).
[0077] (3) The obtained precursor was quickly transferred to a Buchner funnel lined with two filter papers and a 5000 mesh filter cloth, and washed with deionized water (water drop rate 2 drops / second, washed until the ionic conductivity is 20±5us / cm).
[0078] (4) Remove the excess deionized water from the Buchner funnel with a pump and transfer it to a 500ml jacketed beaker, add 100ml deionized water and stir at 500rpm for 20mins to disperse the precursor. Under low temperature conditions, add 50ml of 30% hydrogen peroxide to the precursor dispersion at a rate of 1 drop / 2 seconds at a stirring speed of 350rpm. After the hydrogen peroxide is added in 20 minutes, continue stirring for 20 minutes, continue to add 1.1ml ammonia solution (0.55ml ammonia + 0.55ml water) to adjust the pH value of the solution to 6, and then continue stirring for 10 minutes. Finally, filter it with a sand core funnel equipped with a 0.2um water filter membrane and transfer it to a polytetrafluoroethylene liner and hydrothermally heat it at 200℃ for 12h to obtain titanium oxide, which is named TiO2-1.1ml ammonia.
[0079] The method provided in Example 1 is consistent with the synthesis method of the above-mentioned standard titanium oxide compared with the above-mentioned comparative example 1, except that in the fourth step, after the hydrogen peroxide is added dropwise and stirred for 20 minutes, 1.1 ml of ammonia solution (0.55 ml of ammonia water + 0.55 ml of water) is added to adjust the pH value to 6, and then the stirring is continued for 10 minutes. After filtering with a 0.2 um water filter membrane and a sand core funnel, it is transferred to a polytetrafluoroethylene liner and hydroheated at 200°C for 12 hours to obtain titanium oxide, which is named TiO2-1.1 ml of ammonia water.
[0080] Titanium oxide nanoparticles prepared in Example 1 and Comparative Example 1 were used to prepare titanium oxide nanofilms, as shown below:
[0081] 1. Preparation of titanium oxide nanofilm:
[0082] The titanium oxide nanoparticles obtained by hydrothermal treatment were washed with deionized water and anhydrous ethanol for one and three times by ultrasonic centrifugation, respectively, and the water in the product was replaced with anhydrous ethanol. Then, the titanium oxide nanoparticles were dispersed in 150 ml of anhydrous ethanol, and terpineol and dissolved ethyl cellulose were added in a certain mass ratio (M TiO2 :M terpilenol :M EC =1:14:0.7), ultrasonically treat the prepared material for 30 minutes, filter it with a 12500 mesh filter cloth, and then homogenize it with a homogenizer for five and a half minutes to make the particles more evenly dispersed. The homogenized slurry is rotary evaporated to remove excess ethanol to obtain a finished slurry. The slurry is printed on a conductive glass using screen printing technology to obtain a titanium oxide nanofilm. The specific structure of the perovskite solar cell is as follows: Figure 1 shown.
[0083] The scanning electron microscope (SEM) image of the prepared titanium oxide nanofilm is as follows: Figure 2 As shown, most of the particle sizes of TiO2-C are distributed in the range of 25-45nm, and most of the particle sizes of TiO2-1.1ml ammonia water are distributed in the range of 25-60nm. The nanoparticles of the two are evenly dispersed, and the particle size of the latter is slightly larger than that of the former. The titanium oxide nanoparticles with uniform particle size of about 50nm synthesized in this patent create a porous structure with suitable pore size in the titanium oxide film, which not only helps to fill the perovskite solution, but also allows a sufficiently large interface contact area between the titanium oxide particles and the perovskite to facilitate the extraction and transmission of carriers, thereby avoiding the problem that the perovskite solution cannot be filled into the electron transport layer due to the small particle size, and the perovskite has many crystal defects due to the large particle size.
[0084] according to Figure 3 As shown in the XRD, adding ammonia water will make the anatase phase of the particles stronger, while the rutile phase disappears, which is beneficial to the increase of the current in the battery. The synthesis method is optimized by adding ammonia water to adjust the pH of the precursor in a simple and quick way, so that all the rutile phases except the anatase phase in the TiO2 nanoparticles are transformed into the anatase phase. In this process, the pH value of the precursor mainly affects the polymerization mode of the TiO6 unit. The increase in pH helps its coplanar polymerization to form anatase phase TiO2. Compared with the rutile phase, the anatase phase of TiO2 has a lower effective electron mass, which makes the TiO2 nanoparticles have a higher electron mobility.
[0085] The device efficiency of the TiO2 prepared in the above Example 1 and Comparative Example 1 applied to the perovskite solar cell was characterized, and the results are shown in Table 1 below:
[0086] Table 1 Results of different embodiments and comparative examples
[0087]
[0088] It is not difficult to see from the results given in Table 1 that the method provided by the present invention has a higher photoelectric conversion efficiency (PCE, which refers to the efficiency of converting light energy into electrical energy), and the average current and average fill factor (one of the important parameters of solar cells, which is the ratio of the product of the current and voltage corresponding to the maximum energy output point to the product of the short-circuit current and the open-circuit voltage) are both higher. Moreover, the preparation conditions of the method provided by the present invention are mild and simple, and it is highly operable and practical. From the table, it can be seen that the titanium oxide nanoparticles synthesized after adding ammonia water to adjust the pH have greatly improved current and fill factor compared to the comparative example, which is due to the phase transition of the titanium oxide particles (the rutile phase disappears, and the anatase phase is stronger). The anatase phase has a stronger electron mobility, which makes it transmit electrons faster, alleviating the recombination of electron-hole pairs at the interface of the titanium oxide particles and the perovskite.
[0089] Example 2
[0090] Example 2 provides a method for synthesizing titanium oxide nanoparticles using a mild hydrothermal method, comprising:
[0091] (1) Take a 100 ml jacketed beaker, use a low temperature cooling circulation pump (DLSB-5L / 20) to pass condensed water, take 15 ml of deionized water and add it. After the water temperature drops to the target temperature, prepare for the next step.
[0092] (2) Under stirring at 500 rpm, add 5 ml of 2M TiCl4 to the deionized water in the first step at a rate of 1 drop / second. After stirring for 10 minutes, use a constant pressure funnel to add 7.2 ml (3.6 ml of ammonia water + 3.6 ml of deionized water) of ammonia solution to obtain a white Ti(OH)4 solid. (During the titration of ammonia solution, the drop rate is 1 drop / 6 seconds; the drop time is 10 minutes).
[0093] (3) The obtained precursor was quickly transferred to a Buchner funnel lined with two filter papers and a 5000 mesh filter cloth, and washed with deionized water (water drop rate 2 drops / second, washed until the ionic conductivity is 20±5us / cm).
[0094] (4) Use a pump to remove excess deionized water from the Buchner funnel and transfer it to a 500 ml jacketed beaker. Add 100 ml of deionized water and stir at 500 rpm for 20 mins to disperse the precursor. Under low temperature conditions, 50 ml of 30% hydrogen peroxide was added to the precursor dispersion at a rate of 1 drop / 2 seconds at a stirring speed of 350 rpm. After the hydrogen peroxide was added for 20 minutes, stirring was continued for 20 minutes, and different volumes of ammonia solution (1.1 ml / 2.3 ml / 4.7 ml / 9.5 ml ammonia solution) were continued to be added (half ammonia solution + half deionized water), or 8 ml of 2M hydrochloric acid solution was directly added to adjust the pH of the solution, and then stirring was continued for 10 minutes. Finally, it was filtered with a 0.2 um water filter membrane and a sand core funnel, and then transferred to a polytetrafluoroethylene liner and hydrothermally heated at 200°C for 12 hours to obtain titanium oxide, which was named TiO2-Xml ammonia solution / TiO2-8ml hydrochloric acid (X is 1.1 ml / 2.3 ml / 4.7 ml / 9.5 ml).
[0095] The method provided in Example 2 is compared with Example 1, and the difference of titanium oxide nanoparticles prepared after adding different volumes of ammonia solution or hydrochloric acid in the fourth step is compared on the basis of Example 1. The method provided in Example 2 is consistent with the synthesis method of the above-mentioned standard titanium oxide, except that in the fourth step, after adding hydrogen peroxide and stirring for 20 minutes, different volumes of ammonia solution are added (the amount of ammonia solution is increased to 2.3ml / 4.7ml / 9.5ml), or 8ml of 2M hydrochloric acid is added, and then stirring is continued for 10mins, and filtered with a 0.2um water filter membrane and a sand core funnel, and then transferred to a polytetrafluoroethylene liner and hydrothermal at 200℃ for 12h to obtain titanium oxide, which is named TiO2-Xml ammonia solution / TiO2-8ml hydrochloric acid (X is 1.1ml / 2.3ml / 4.7ml / 9.5ml).
[0096] Titanium oxide nanoparticles prepared in Example 2 were used to prepare titanium oxide nanofilms, as shown below:
[0097] 1. Preparation of titanium oxide nanofilm:
[0098] The titanium oxide nanoparticles obtained by hydrothermal treatment were washed with deionized water and anhydrous ethanol for one and three times by ultrasonic centrifugation, respectively, and the water in the product was replaced with anhydrous ethanol. Then, the titanium oxide nanoparticles were dispersed in 150 ml of anhydrous ethanol, and terpineol and dissolved ethyl cellulose were added in a certain mass ratio (M TiO2 :M terpilenol :M EC=1:14:0.7), ultrasonically treat the prepared material for 30 minutes, filter it with a 12500 mesh filter cloth, and then homogenize it with a homogenizer for five and a half minutes to make the particles more evenly dispersed. The homogenized slurry is rotary evaporated to remove excess ethanol to obtain a finished slurry. The slurry is printed on a conductive glass using screen printing technology to obtain a titanium oxide nanofilm. The specific structure of the perovskite solar cell is as follows: Figure 1 shown.
[0099] The scanning electron microscope (SEM) image of the prepared titanium oxide nanofilm is as follows: Figure 4 As shown. Combined Figure 4 It is not difficult to see that with the increase of ammonia water, many rod-shaped titanium oxides are generated while the nanoparticles grow, which is caused by the directional attachment of hydroxide. The particle size of TiO2-C is about 40nm, and the particle size of 1.1ml titanium oxide is about 40-50nm, which is in line with the expected particle size. The particle size of 4.7ml and 9.5ml titanium oxide particles is about 50-200nm, which is too large to be used as an electron transport layer. 8ml 1MHCl-TiO2 also has many rod-shaped particles, which may be rod-shaped rutile phase titanium oxide.
[0100] Figure 5 The XRD result corresponding to Example 2. According to the XRD results shown, when the precursor is acidic, the product is a mixed phase of anatase phase and rutile phase, and the crystallinity and crystalline content of anatase phase TiO2 are positively correlated with the amount of ammonia added. By simply adjusting a series of pH values, the changes in the titanium oxide phase and particle size morphology under different pH values were verified, and the optimal pH condition was found.
[0101] The device efficiency of the TiO2 prepared in the above Example 2 applied to the perovskite solar cell was characterized, and the results are shown in Table 2 below:
[0102] Table 2 Results of different embodiments and comparative examples
[0103]
[0104]
[0105] It is not difficult to see from the results given in Table 2 above that the average efficiency of titanium oxide with 1.1ml and 2.3ml ammonia water can reach 15.600 and 15.97 respectively, which are higher than other samples. Adding ammonia water to the precursor solution PTC is conducive to the increase of current, while adding hydrochloric acid reduces the current. This is closely related to the crystal phase of titanium oxide particles, because adding alkali promotes the crystallization of anatase titanium oxide, and adding hydrochloric acid is conducive to the crystallization of rutile phase. The effective electron mass of anatase is low and the electron mobility is large, which will make the current of solar cells prepared by anatase titanium oxide higher.
[0106] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "examples", "specific implementations", or "some implementations" means that the specific features, structures, materials, or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials, or characteristics described may be combined in any one or more embodiments or examples in a suitable manner.
[0107] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations of the present invention. A person skilled in the art may change, modify, replace and vary the above embodiments within the scope of the present invention.
Claims
1. A method for synthesizing titanium oxide nanoparticles by a mild hydrothermal method, characterized in that: include: (1) Under low temperature conditions, TiCl4 is added dropwise to deionized water, and after stirring, an ammonia solution is added dropwise to obtain Ti(OH)4 solid; (2) washing the Ti(OH)4 solid by dripping with a Buchner funnel and dispersing it with deionized water to obtain a precursor dispersion; (3) Under low temperature conditions, hydrogen peroxide is added dropwise to the precursor dispersion, and then an ammonia solution is added to adjust the pH value to 5.5-6.5, and hydrothermal treatment is performed at a predetermined temperature to obtain titanium oxide nanoparticles, wherein the predetermined temperature is 190-210 degrees Celsius.
2. The method according to claim 1, characterized in that The ammonia solution in step (1) is an ammonia solution having a volume concentration of 40 v / v% to 60 v / v%; Optionally, the ammonia solution in step (3) is an ammonia solution having an ammonia volume concentration of 40 v / v% to 60 v / v%; Optionally, the volume of the aqueous ammonia solution in step (3) is 1% to 3% of the volume of the precursor dispersion.
3. The method according to claim 1, characterized in that The low temperature condition in step (1) is 0 to 4 degrees Celsius; Optionally, the low temperature condition in step (3) is 0 to 4 degrees Celsius.
4. The method according to claim 1, characterized in that: The mass fraction of the hydrogen peroxide in step (3) is 25 w / w% to 35 w / w%.
5. The method according to claim 1, characterized in that The particle size of the titanium oxide nanoparticles is 20 to 70 nanometers, preferably 25 to 60 nanometers.
6. The method according to claim 1, characterized in that The predetermined temperature is 195-205 degrees Celsius, preferably 200 degrees Celsius.
7. A titanium oxide nanoparticle, characterized in that: Prepared according to the method according to any one of claims 1 to 6.
8. A conductive paste, characterized in that: Comprising the titanium oxide nanoparticles according to claim 7.
9. A titanium oxide nanofilm, characterized in that: The titanium oxide nanofilm is prepared using the conductive paste described in claim 8.
10. A perovskite solar cell, characterized in that: include: basal layer; A hole blocking layer, the hole blocking layer is located on the surface of the base layer, and the hole blocking layer comprises the titanium oxide nanofilm according to claim 9; A mesoporous electron transport layer, wherein the mesoporous electron transport layer is located on the surface of the hole blocking layer; A mesoporous spacer layer, wherein the mesoporous spacer layer is located on the surface of the mesoporous electron transport layer; A porous back electrode layer, wherein the porous back electrode layer is located on the surface of the mesoporous spacer layer; as well as The perovskite film layer is located in the mesopores of the mesoporous electron transport layer, the mesoporous spacer layer and the porous back electrode layer.
